THE FUTURE OF WORKPLACE WELL-BEING: A SCOPUS-AI REVIEW ON EMOTIONAL INTELLIGENCE AND AI-DRIVEN HAPPINESS MANAGEMENT - Mat Khairi, Siti Murni; Salleh, Shazwani Mohd; Rozali, Norhasyikin; Abdul Jalil, Muna; Zainuddin, Argustina (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The rapid evolution of workplace dynamics, driven by technological advancements and shifting employee expectations, has underscored the importance of workplace well-being as a cornerstone of organizational success. However, while emotional intelligence (EI) has long been recognized as a critical factor in fostering workplace well-being, its integration with artificial intelligence (AI)-driven happiness management remains underexplored. This study aims to address this gap by examining the role of emotional intelligence in enhancing workplace well-being, exploring the potential of AI to promote employee happiness, and identifying strategies for integrating EI and AI to create supportive work environments. A systematic literature review was conducted using Scopus AI data-driven analytics. The findings reveal that emotional intelligence significantly contributes to mental health, work engagement, and satisfaction with social support, while AI offers scalable solutions for monitoring well-being and delivering personalized interventions. The integration of EI and AI creates synergistic effects, enabling organizations to design empathetic and data-driven strategies that balance human-centric values with technological efficiency. The study highlights practical implications for leaders and organizations, emphasizing the importance of EI training programs and ethical AI adoption to build trust and enhance employee happiness. Despite its contributions, the study acknowledges limitations, including potential selection bias and underrepresentation of cultural and sector-specific nuances. Future research should explore longitudinal effects, ethical considerations, and the role of emerging technologies in promoting emotional awareness. By bridging emotional intelligence and AI-driven happiness management, this study provides a foundation for creating workplaces that prioritize employee well-being, productivity, and sustainable success.